Different Crystallographic One-dimensional MnO2 Nanomaterials and Their Superior Performance in Catalytic Phenol Degradation - Saputra, E.; Muhammad, S.; Sun, Hongqi; Ang, Ha Ming; Tade, Moses; Wang, Shaobin (American Chemical Society, 2013)
Three one-dimensional MnO2 nanoparticles with different crystallographic phases, alpha-, beta-, and gamma-MnO2, were synthesized, characterized, and tested in heterogeneous activation of Oxone for phenol degradation in aqueous solution. The alpha-, beta-, and gamma-MnO2 nanostructured materials presented in morphologies of nanowires, nanorods, and nanofibers, respectively. They showed varying activities in activation of Oxone to generate sulfate radicals for phenol degradation depending on surface area and crystalline structure. alpha-MnO2 nanowires exhibited the highest activity and could degrade phenol in 60 min at phenol concentrations ranging in 25-100 mg/L. It was found that phenol degradation on alpha-MnO2 followed first order kinetics with an activation energy of 21.9 kJ/mol. The operational parameters, such as MnO2 and Oxone loading, phenol concentration and temperature, were found to influence phenol degradation efficiency. It was also found that alpha-MnO2 exhibited high stability in recycled tests without losing activity, demonstrating itself to be a superior heterogeneous catalyst to the toxic Co3O4 and Co2+.